Continuing professional development of physical education teachers through collaborative professional reflection - Nataliia Mukan; Fedir Zagura; Yuliana Lavrysh (Millenium)
Introduction: This paper explores the pivotal role of continual reflection and collaboration for physical education teachers in advancing their professional development. The study focuses on the effectiveness of Gibbs Model and Glatthorn's collegial growth paradigm in enhancing teachers' self-reflection abilities.